Persepsi Norma Sosial Orang Tua Terhadap Perilaku Anak dalam Penerapan Protokol Kesehatan - Renteng, Septriani; Simak, Valen Fridolin; Datu, Ronald Joy (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2021)
The increase in Covid-19 cases is followed by higher risk of exposure to children, resulting in highermortality rate in children. This risk of exposure to children can be lowered by properly implementingthe health and safety protocols. Preschooler behavior and ability to implement health protocolsproperly, is highly determined by parents’ role in giving examples of health protocolsimplementation. One’s behavior is affected by social norms that apply in the society. This studyexamined the effect of perceived social norms among parents on children's behavior in carrying outhealth protocols. This quantitative study was conducted using a cross sectional design, involving 312preschoolers in Manado City as samples. A set of questionaire measuring social norms andchildren's behavior in implementing health protocols was used to collect the data. Data were thenanalyzed using regression test to examine the influence of perceived social norms among parents onchildren's behavior in implementing health protocols (p = 0.000). Results indicated an influence ofperceived social norms among parents on children's behavior in implementing health protocols.